2012
DOI: 10.5296/jse.v2i2.1495
|View full text |Cite
|
Sign up to set email alerts
|

A Generalizability Approach to the Measurement of Score Reliability of the Teacher Assessment Literacy Questionnaire

Abstract: Classroom assessment is one of the main responsibilities of the teachers. Sound classroom assessment practices require teachers to have adequate levels of knowledge and skills in the educational assessment. The Teacher Assessment Literacy Questionnaire (TALQ) was developed by Plake and Impara (1992) to measure teachers' knowledge and understanding of the basic principles of the educational assessment. This study applied generalizability theory to estimate the dependability of the TALQ's scores for pre-service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…The interview findings suggest that teachers' assessment competence is perceived to be modest, with low levels of assessment literacy and practice, and it noted that this assessment literacy impacts students' motivation to learn, and engage, and affects their overall competence. This finding is consistent the results of other studies (Al-Bahlani,2017;Alkharusi, 2011b; 2011c; Alkharusi et al, 2011, Alkharusi et al, 2012Lyon, 2011;Mertler and Campbell, 2005). The study also found that there The overall assessment literacy was deemed low with an average score of 8.81/35 (25%) compared to the overall teachers' perceived practice (competence total mean score 3.11 (moderately competent), practice total mean score 1.66).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The interview findings suggest that teachers' assessment competence is perceived to be modest, with low levels of assessment literacy and practice, and it noted that this assessment literacy impacts students' motivation to learn, and engage, and affects their overall competence. This finding is consistent the results of other studies (Al-Bahlani,2017;Alkharusi, 2011b; 2011c; Alkharusi et al, 2011, Alkharusi et al, 2012Lyon, 2011;Mertler and Campbell, 2005). The study also found that there The overall assessment literacy was deemed low with an average score of 8.81/35 (25%) compared to the overall teachers' perceived practice (competence total mean score 3.11 (moderately competent), practice total mean score 1.66).…”
Section: Discussionsupporting
confidence: 90%
“…In the last research question interview findings supported the quantitative data, indicating that teachers' assessment competence is perceived as modest, impacting students' motivation, engagement, and overall competence. This aligns with previous studies (Al-Bahlani, 2017; Alkharusi, 2011b, 2011c; Alkharusi et al, 2011Alkharusi et al, , 2012Lyon, 2011;Mertler & Campbell, 2005). The study recommended a multifaceted approach, incorporating pre-service, in-service, and continuous professional development to enhance teachers' assessment competence.…”
Section: Discussionsupporting
confidence: 86%
“…This has made assessments important in learning, and would require for lecturers to undertake appropriate assessments on student learning (Stiggins et al, 1989;Popham, 2004a, b;Carey, 1994). The learning outcomes determined by the lecturers are great determinants of the students' destiny as far as their education is concerned (Ames, 1992;Harlen and Crick, 2003;Alkharusi, 2008). The differences discovered in lecturers' assessment competencies and practices in the specialisation of education with other specialisations were expected.…”
Section: Discussionmentioning
confidence: 98%